The Use Of Radio Frequency Transponders In Density Tracers To Conduct Coal Plant Efficiency Analysis - D van der Merwe (The Southern African Institute of Mining and Metallurgy, 2006)
Tracers of known densities are used world wide in coal processing plants to evaluate plant performance. Tracers are added to the feed stream and are counted after being recovered from the product and discard streams to determine partition curves. The need to recover the tracers can be eliminated by adding radio frequency identification tags to the tracers. Readers mounted on the product and discard streams record the passing RF tracers and produce the partition curve instantly. Tests were performed with three different shaped tracers at different collieries on cyclones ranging from 510mm to 800mm in diameter. Sink and float analyses of coal samples were used to compare conventional partition curves to partition curves obtained by using RF tracers. The average amount of tracers recorded was 78% of tracers in the feed. The results indicate that the stone shaped tracers represent the results from the sink-float analyses the best. The results suggest that RF tracers can be used to evaluate cyclone circuits in the coal industry and will make it possible to evaluate a coal circuit?s efficiency without stopping a plant and waiting for laboratory analyses. Keywords Coal tracers, partition curve, radio frequency tracer, RFID